Disease Diagnostics and Potential Coinfections by Vibrio coralliilyticus During an Ongoing Coral Disease Outbreak in Florida - Ushijima, Blake; Meyer, Julie L.; Thompson, Sharon; Pitts, Kelly; Marusich, Michael F.; Tittl, Jessica; Weatherup, Elizabeth; Reu, Jacqueline; Wetzell, Raquel; Aeby, Greta S.; Häse, Claudia C.; Paul, Valerie J. (Frontiers in Microbiology, 2020)
A deadly coral disease outbreak has been devastating the Florida Reef Tract since 2014. This disease, stony coral tissue loss disease (SCTLD), affects at least 22 coral species causing the progressive destruction of tissue. The etiological agents responsible for SCTLD are unidentified, but pathogenic bacteria are suspected. Virulence screens of 400 isolates identified four potentially pathogenic strains of Vibrio spp. subsequently identified as V. coralliilyticus. Strains of this species are known coral pathogens; however, cultures were unable to consistently elicit tissue loss, suggesting an opportunistic role. Using an improved immunoassay, the VcpA RapidTest, a toxic zinc-metalloprotease produced by V. coralliilyticus was detected on 22.3% of disease Montastraea cavernosa (n=67) and 23.5% of diseased Orbicella faveolata (n=24). VcpA+ corals had significantly higher mortality rates and faster disease progression. For VcpA- fragments, 21.6% and 33.3% of M. cavernosa and O. faveolata, respectively, died within 21 d of observation, while 100% of similarly sized VcpA+ fragments of both species died during the same period. Further physiological and genomic analysis found no apparent differences between the Atlantic V. coralliilyticus strains cultured here and pathogens from the Indo-Pacific but highlighted the diversity among strains and their immense genetic potential. In all, V. coralliilyticus is believed to be causing coinfections that exacerbate existing SCTLD lesions, which is contributing to the intraspecific differences observed between colonies. This study describes coinfections contributing to SCTLD virulence as well as diagnostic tools capable of tracking the pathogen involved, which are important contributions to the management and understanding of SCTLD.